Phytoestrogenic Activity of Blackcurrant Anthocyanins Is Partially Mediated through Estrogen Receptor Beta - Naoki Nanashima; Kayo Horie; Hayato Maeda (Molecules, 2017)
Phytoestrogens are plant compounds with estrogenic effects found in many foods. We have previously reported phytoestrogen activity of blackcurrant anthocyanins (cyanidin-3-glucoside, cyanidin-3-rutinoside, delphinidin-3-glucoside, and delphinidin-3-rutinoside) via the estrogen receptor (ER)α. In this study, we investigated the participation of ERβ in the phytoestrogen activity of these anthocyanins. Blackcurrant anthocyanin induced ERβ-mediated transcriptional activity, and the IC50 of ERβ was lower than that of ERα, indicating that blackcurrant anthocyanins have a higher binding affinity to ERβ. In silico docking analysis of cyanidin and delphinidin, the core portions of the compound that fits within the ligand-binding pocket of ERβ, showed that similarly to 17β-estradiol, hydrogen bonds formed with the ERβ residues Glu305, Arg346, and His475. No fitting placement of glucoside or rutinoside sugar chains within the ligand-binding pocket of ERβ-estradiol complex was detected. However, as the conformation of helices 3 and 12 in ERβ varies depending on the ligand, we suggest that the surrounding structure, including these helices, adopts a conformation capable of accommodating glucoside or rutinoside. Comparison of ERα and ERβ docking structures revealed that the selectivity for ERβ is higher than that for ERα, similar to genistein. These results show that blackcurrant anthocyanins exert phytoestrogen activity via ERβ.